Binge‐eating disorder with and without lifetime anorexia nervosa: A comparison of sociodemographic and clinical features. Issue 2 (29th November 2022) - Pawar, Pratiksha S.; Thornton, Laura M.; Flatt, Rachael E.; Sanzari, Christina M.; Carrino, Emily A.; Tregarthen, Jenna P.; Argue, Stuart; Bulik, Cynthia M.; Watson, Hunna J.
Abstract: Objective: To compare individuals who have experienced binge‐eating disorder (BED) and anorexia nervosa (AN) (BED AN+) to those who have experienced BED and not AN (BED AN–). Method: Participants ( N = 898) met criteria for lifetime BED and reported current binge eating. Approximately 14% had a lifetime diagnosis of AN. Analyses compared BED AN+ and BED AN– on sociodemographic variables and clinical history. Results: The presence of lifetime AN was associated with more severe eating disorder symptoms, including earlier onset, more frequent, more chronic, and more types of eating disorder behaviors over the lifetime, as well as a higher lifetime prevalence of bulimia nervosa (BN). Participants with lifetime AN reported being more likely to have received treatments for BED or BN, had significantly lower minimum, current, and maximum BMIs, had more severe general anxiety, and were significantly more likely to be younger and female. In the full sample, the lifetime prevalence of unhealthy weight control behaviors was high and treatment utilization was low, despite an average 15‐year history since symptom onset. Gastrointestinal disorders and comorbid anxiety, depression, and attention‐deficit/hyperactivity disorder symptoms were prevalent. Discussion: Individuals fared poorly on a wide array of domains, yet those with lifetime AN fared considerably more poorly. All patients with BED should be screened for mental health and gastrointestinal comorbidities and offered referral and treatment options. Public Significance: Individuals experiencing binge‐eating disorder have severe symptomology, but those who have experienced binge‐eating disorder and anorexia nervosa fare even more poorly. Our study emphasizes that patients with binge‐eating disorder would benefit from being screened for mental health and gastrointestinal comorbidities, and clinicians should consider history of unhealthy weight control behaviors to inform treatment and relapse prevention.